Electric potential distributions in space charge regions of molecular organic adsorbates using a simplified distributed states model. Issue 9 (26th March 2014) - Mankel, Eric; Hein, Corinna; Kühn, Maybritt; Mayer, Thomas
<x xml:space="preserve">Abstract</x> We study the evolution of the electric surface potential for small molecular organic semiconductors adsorbed on different high‐work function substrates using photoelectron spectroscopy. Usually, the surface potential of these materials shows a typical progression in dependence of the adsorbate layer thickness indicating the formation of a space charge region near the interface. We discuss the surface potential evolution on the basis of the commonly used Schottky model and a second model using a density of states distribution (DOS) in the adsorbed semiconductor energy gap. In order to derive an analytical solution, we simplify an existing approach for space charge regions at polymer contacts. This approach is based on tailing gap states in polymer adsorbates. We simplify it using a constant DOS distribution. The differences between the Schottky model and the simplified distributed states model will be discussed. Finally, both models are applied to measured values of the surface potential evolution of some exemplary organic molecules on different substrates. We find that the surface potential evolution of the simplified distributed states model describes the measured potential development more accurately than the Schottky model. The DOS is estimated in the framework of the model being between 1018 and 1019 cm−3 eV−1.